The fluorination effect of fluoroamphiphiles in cytosolic protein delivery - Zhang, Zhenjing; Shen, Wanwan; Ling, Jing; Yan, Yang; Hu, Jingjing; Cheng, Yiyun (Nature communications, 2018)
Direct delivery of proteins into cells avoids many drawbacks of gene delivery, and thus has emerging applications in biotherapy. However, it remains a challenging task owing to limited charges and relatively large size of proteins. Here, we report an efficient protein delivery system via the co-assembly of fluoroamphiphiles and proteins into nanoparticles. Fluorous substituents on the amphiphiles play essential roles in the formation of uniform nanoparticles, avoiding protein denaturation, efficient endocytosis, and maintaining low cytotoxicity. Structure-activity relationship studies reveal that longer fluorous chain length and higher fluorination degree contribute to more efficient protein delivery, but excess fluorophilicity on the polymer leads to the pre-assembly of fluoroamphiphiles into stable vesicles, and thus failed protein encapsulation and cytosolic delivery. This study highlights the advantage of fluoroamphiphiles over other existing strategies for intracellular protein delivery. Proteins can serve as means of medical treatment, but their efficient delivery to cells is difficult. Here, the authors present a type of polymers, fluoroamphiphiles, acting as chemical chaperones that can facilitate the import of proteins into the inner compartment, i.e. cytosol, of cells.